Multi-detector CT and MRI of microembolized myocardial infarct: monitoring of left ventricular function, perfusion, and myocardial viability in a swine model. (February 2016) - Saeed, Maythem; Bajwa, Hisham Z; Do, Loi; Hetts, Steven W; Wilson, Mark W
Background: Patients with acute myocardial infarct (MI) show additional damage after coronary interventions. Purpose: To longitudinally quantify structural and functional changes in the left ventricle (LV) subjected to microembolized MI using multidisciplinary computed tomography (MDCT) and independent reference methods. Material and Methods: Swine ( n = 20) served as controls (group I) or were subjected to a combination of coronary occlusion, microembolization, and reperfusion and imaged at 3 days (group II) or 3 days and 5 weeks (group III). LV volumes, perfusion, and MI mass were quantified on cine, perfusion, and delayed contrast enhancement (DE) MDCT. MRI, cardiac injury biomarkers, histochemical and histopathologic stains were used as independent references. Results: MDCT showed a reduction in ejection fraction and increased end systolic volume (31 ± 2% and 82 ± 3 mL, respectively) of group III compared with I (48 ± 2% and 57 ± 1 mL, respectively). It also demonstrated perfusion deficits in microembolized MI and peri-infarcts. DE-MDCT delineated microvascular obstruction (MVO) zones embedded in acute microembolized MI and microinfarct specks resulting from persistent MVO by deposited microemboli in microvessels of peri-infarct zone. Bland-Altman test showed close agreements between the extents of microembolized MI measured on DE-MDCT, DE-MRI, and histochemical TTC staining, but not between these modalities and microscopy. MI resorption was evident between 3 days and 5 weeks (13.4 ± 0.5 g and 9.8 ± 0.5 g, P < 0.017) and histologic examination revealed incomplete healing. Injury biomarkers were increased after intervention. Conclusion: MDCT can longitudinally quantify regional perfusion deficits, LV dysfunction, and resorption of microembolized MI. MDCT or MRI can be used alternatively after coronary interventions in cases of contraindications for one modality or the other.